Phase-shift full bridge power supply based on SiC devices - Liu, Guobing; Wang, Kui; Qu, Cangqi; Liu, Shaogang; Jia, Qi; Li, Yongdong (Journal of engineering (Stevenage, England), 2018)
In order to accurately obtain the switching characteristics of SiC MOSFET in practical application, a dual pulse test circuit is used to test the SiC MOSFET in this subject. By analysing the double pulse test circuit and taking into account the parasitic parameters, the effects of different gate resistances (Rg) and the capacitance between gate and source (Cgs) on the switching characteristics of the SiC MOSFET are summarised. Also, a phase-shifted full-bridge power supply based on SiC device is designed, which can be changed from 270 V direct current (DC) to 220 V alternating current (AC)/50 Hz, which consists of two stages. The first stage is the phase shifted full bridge ZVS DC/DC converter, which will boost the 270 V DC to the 350 V DC; the latter is a single-phase full bridge inverter, and the 350 V DC will be converted to the 220 V AC/50 Hz. The power supply uses the SiC MOSFET as the switch tube, which can reduce the switching loss, improve the switching frequency and reduce the volume of the transformer. A rectifier circuit using a SiC Schottky diode, with almost no reverse recovery process, greatly reduced the transformer side parasitic oscillation and improved the efficiency of the power supply. In this study, the design method of the parameters of the power supply is described in detail. Finally, the rationality of the design of the power supply parameters is verified by MATLAB/Simulink simulation and experimental prototypes.